2003
DOI: 10.1002/pmic.200300410
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of secreted proteins during osteoclast differentiation using two different methods: Two‐dimensional electrophoresis and isotope‐coded affinity tags analysis with two‐dimensional chromatography

Abstract: Bone is maintained by two cell types, bone-forming osteoblasts and bone-resorbing osteoclasts. Osteoblasts express two factors, osteoprotegerin and receptor activator of NF-kappaB ligand (RANKL), inhibiting and promoting osteoclast differentiation, respectively. In contrast, modulators of bone resorption expressed by osteoclasts have not been so well studied enough. In the present study, we demonstrate proteome analysis of secreted proteins during osteoclast differentiation to elucidate the molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 45 publications
5
61
2
1
Order By: Relevance
“…5 Because proteins presented in bone tissue are essential for all life processes of bone and are the most important final products of the information pathways, profiling those proteins is vital to understand the bone biology thoroughly. However, proteome research on bone is mainly focused on in vitro systems using bone cells, [6][7][8][9] such as osteoblasts and osteoclasts, to determine which proteins are expressed by a cell type under given experimental conditions, but they cannot establish what the actual protein profile of bone is. Recently, the extraction of proteins directly from bone for proteome analysis had been reported.…”
Section: Introductionmentioning
confidence: 99%
“…5 Because proteins presented in bone tissue are essential for all life processes of bone and are the most important final products of the information pathways, profiling those proteins is vital to understand the bone biology thoroughly. However, proteome research on bone is mainly focused on in vitro systems using bone cells, [6][7][8][9] such as osteoblasts and osteoclasts, to determine which proteins are expressed by a cell type under given experimental conditions, but they cannot establish what the actual protein profile of bone is. Recently, the extraction of proteins directly from bone for proteome analysis had been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Profiling those proteins is vital for a thorough understanding of bone biology. To date, proteome research on bone has been focused mainly on in vitro analysis of bone-forming cells (osteoblasts and osteoclasts) to determine which proteins are expressed under a given set of experimental conditions (13)(14)(15)(16). Although important, such studies cannot identify the actual protein profile in oral alveolar bone.…”
mentioning
confidence: 99%
“…Martin et al, 97 have used a combination of ICAT and tandem mass spectrometry to identify and quantitate a comprehensive list of over 500 proteins, which were secreted from neoplastic prostate cancer cell line (LNCaP) in the presence or absence of androgen receptor stimulation. Similar studies have identified numerous secreted proteins during differentiation of 3T3-L1 preadipocytes to adipocytes, 98 in response to calcium-dependent secretion in human neutrophils, 99 during osteoclast differentiation 100 and astrocytes. 101 Cell surface proteome Proteomic approaches for the comprehensive profiling and identification of proteins on cell surface or membranes have been reported.…”
Section: Secretomementioning
confidence: 78%